2022
DOI: 10.3390/medicina59010095
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Complete Coverage Tooth-Retained Fixed Lithium Disilicate Prostheses: A Systematic Review

Abstract: Background and objectives: Porcelain-fused-to-metal (PFM) prostheses are considered the gold standard for the replacement of missing teeth, however, these have several drawbacks. Therefore, lithium disilicate (LDS) prostheses have been introduced for the construction of fixed crowns and bridges. The aim of this systematic review was to ascertain the long-term survival of LDS fixed prostheses in comparison to other materials. Materials and methods: The focused question was ‘In patients who have undergone prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…All‐ceramic crowns have been used widely in dentistry with similar clinical success rate to metal‐ceramic crowns. Their survival rate in the anterior region after 11 years is 98.9% 26 . It has been reported that after 10 years of clinical service, need to re‐intervention without replacement in ceramic veneers occurs in 36% of ceramic veneers, and only 7% of ceramic veneers get a more invasive treatment approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All‐ceramic crowns have been used widely in dentistry with similar clinical success rate to metal‐ceramic crowns. Their survival rate in the anterior region after 11 years is 98.9% 26 . It has been reported that after 10 years of clinical service, need to re‐intervention without replacement in ceramic veneers occurs in 36% of ceramic veneers, and only 7% of ceramic veneers get a more invasive treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Their survival rate in the anterior region after 11 years is 98.9%. 26 It has been reported that after 10 years of clinical service, need to re‐intervention without replacement in ceramic veneers occurs in 36% of ceramic veneers, and only 7% of ceramic veneers get a more invasive treatment approach. The main causes of ceramic veneer failure include fracture, chipping, microleakage, secondary caries and debonding.…”
Section: Discussionmentioning
confidence: 99%